Pre-conditioning with PQQ during pregnancy alleviates LPS-induced placental damage and improves the fetal survival and growth in mice - Han, Yongli; Zhu, Yan; Lu, Xiaohui; Fan, Tingting; Yin, Yina; Liu, Pengfei; Dai, Xiuliang; Xu, Hongbin (Frontiers in Endocrinology, 2025)
BackgroundIntrauterine infection is a major cause of preterm birth, fetal demise, and growth restriction. Placental damage resulting from such infections plays a central role in mediating these adverse outcomes. Pyrroloquinoline quinone (PQQ) is a naturally occurring nutrient known for its antioxidant, anti-inflammatory, and mitochondrial-supporting properties. This study aimed to investigate whether pre-conditioning with PQQ during pregnancy could mitigate adverse effects induced by lipopolysaccharide (LPS)-mediated inflammation in mice.MethodsPregnant mice were randomly assigned to three groups: control, LPS, and LPS + PQQ. On gestational day (GD) 16.5, mice in the LPS groups were intraperitoneally injected with either a single dose of 3 μg/mouse (moderate inflammation) or two doses of 3ug/mouse (severe inflammation) of LPS. In the LPS + PQQ group, PQQ was administered daily from GD 0.5. Outcomes assessed included labor time, fetal survival, fetal and placental weights. Placental structure, vascular networks, inflammation, oxidative stress, and gene expression profiles were evaluated using H&E staining, immunohistochemistry, Prussian blue staining, and RNA sequencing.ResultsPre-conditioning with PQQ significantly alleviated LPS-induced fetal demise and reduced fetal and placental growth. PQQ also improved placental morphology, restored vascular integrity, and normalized aberrant gene expression profiles. Furthermore, PQQ treatment markedly reduced placental inflammation and oxidative stress in mice exposed to moderate LPS. However, under high-dose LPS conditions, PQQ failed to confer significant protective effects.ConclusionOur findings suggest that Pre-conditioning with PQQ during pregnancy can protect against inflammation-induced placental damage and improve fetal survival and growth under moderate inflammatory conditions. This study provides compelling proof-of-concept that PQQ buffers the placenta against maternal systemic inflammatory insults. However, its efficacy appears limited in the context of severe inflammation.